The Effect Of Leverage And Liquidity On Company Value With Company Size As A Moderating Variable On Property And Real Estate Companies Listed On The Indonesia Stock Exchange In 2015-2020 - vina; Nagian Toni; Galumbang Hutagalung (TRIGIN PUBLISHER, 2022)
This study aims to examine and analyze the effect of leverage and liquidity on firm value with firm size as a moderating variable in property and real estate companies listed on the Indonesia Stock Exchange in 2015-2020. The sample of property and real estate is 12 companies, in a period of 6 years. The sampling technique is the Purposive Sampling Technique. The data collection technique is a documentation study with the type of data, namely secondary data. This research uses Partial Least Square data analysis method. And the data is processed with Smart PLS. The results of this study indicate that Leverage has a positive and significant effect on Price to Book Value, Liquidity has a positive and significant effect on Price to Book Value. Then the results of this study also show that Firm Size is not able to moderate the effect of Leverage and Liquidity on Firm Value. The amount of PBV variation can be explained by the independent variable of 5.4% and 94.6% can be explained by other variables such as Total Asset Turnover and others